1993
DOI: 10.1002/anie.199317771
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Analysis of Model Complexes for Methyl‐Coenzyme‐M Reductase from Methanogenic Bacteria: A Comparison of Crystal and Solution Structures

Abstract: In the last step of the archaebacterial methanogenesis, the methylthioether methyl-coenzyme-M 1 reacts with the thiol N-7-mercaptoheptanoyl-0-phospho-L-threonine ("HS-HTP", 2) to yield methane and the mixed disulfide 3. ['] This unusual reaction is brought about by the enzyme methyl-coenzyme-M reductase, which contains the nickel tetrahydrocorphinoid "factor 430" (F430) as cofactor.[21 In general, metalloenzyme-mediated catalysis depends on the specific interaction between substrate(s) and metal ion(s). Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The study of their protonated analogues (and their derivatives) is therefore also relevant to a better understanding of protolytic activation of the related biological systems. Recently, Thauer et al have suggested that protosolvolytic activation may play an important role in some enzyme catalytic reactions …”
Section: Resultsmentioning
confidence: 99%
“…The study of their protonated analogues (and their derivatives) is therefore also relevant to a better understanding of protolytic activation of the related biological systems. Recently, Thauer et al have suggested that protosolvolytic activation may play an important role in some enzyme catalytic reactions …”
Section: Resultsmentioning
confidence: 99%
“…For example, a recently discovered metal-free hydrogenase enzyme catalyzes the reversible dehydrogenation of methylenetetrahydromethaneopterin (CH 2 H 4 MPT) to methenyltetrahydromethanopterin (CHH 4 MPT + ) and H 2 . It was suggested that the amidinium ion entity is further activated by N-protonation in the enzyme to bind a H 2 molecule via a two-electron, three-center (2e-3c) bond . The present experimental and theoretical study of protonated guanidines is therefore also relevant to a better understanding of protolytic activation of guanidine containing biological systems.…”
Section: Introductionmentioning
confidence: 83%
“…In superelectrophilic activation, nonbonded electron pairs on onium ions further interact with Brönsted or Lewis acids and in the limiting case can lead to gitonic dications (polycations), i.e., proximal as contrasted with conventional distonic (distant) dications. In their studies Berkessel and Thauer have suggested that such activation may also play an important role in some enzyme catalytic reactions . For example, a recently discovered metal-free hydrogenase enzyme catalyzes the reversible dehydrogenation of methylenetetrahydromethaneopterin (CH 2 H 4 MPT) to methenyltetrahydromethanopterin (CHH 4 MPT + ) and H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…With increasing size the tension in the macrocycle of F 430 decreases and the ring becomes planar, as in high-spin Ni(II)F 430 and Ni(I)F 430 [46]. Different conformations of the ring system and its consequences have also been studied in Ni(II)F 430 model compounds [62,[64][65][66][67][68][69].…”
Section: Properties Of Ni(ii)f 430 and Nonplanaritymentioning
confidence: 99%